The Prevalence of the Hepatitis B Core Antibody and the Occult Hepatitis B Infection Among Voluntary Blood Donors in Chennai, India - KS, Maheswari (JCDR Research and Publications (P) Limited, 2012)
INTRODUCTION: The infection with the Hepatitis B Virus (HBV) is a global health problem which affects 2 billion people worldwide. In India, the prevalence of the Hepatitis B infection is 4% in the general population. The prevalence of the HBV infection in voluntary blood donors is 1-3%. It has been reported that the viraemia continues even after the clinical recovery from the acute HBV infection. Some blood donors who were negative for the surface antigen but positive for the core antibody have been reported to transmit HBV, leading to acute hepatitis. This study was done to determine the seroprevalence of the hepatitis B core antibody in voluntary blood donors in Chennai, India. MATERIALS AND METHOD: This prospective study was conducted in our department during 2008-2009. A total of 9100 donor samples were screened for the Hepatitis B surface antigen and the Hepatitis B core antibody (IgM and IgG) by ELISA. The samples which were positive for the core antibody were subjected to Real-time PCR for the Hepatitis B DNA detection. RESULTS: Among the 9100 donors, 911 (10.01%) donors were positive for the core antibody. The Hepatitis B Surface antigen was positive in 199 (2.18%) donors. Among the 911 donors who were positive for the core antibody, 820 (90.01%) donors were negative for the HBsAg and 2 donors were positive for Hepatitis B DNA. CONCLUSION: If a routine screening of the sera for the core antibody is not done, the low-level HBV viraemia may not be identified. The absence of the surface antigen in the blood of apparently healthy individuals may not be sufficient to ensure the lack of the circulating virus.